An interdisciplinary approach to investigate collective cell migration in neural crest - Giniūnaitė, R; McLennan, R; McKinney, M; Baker, R; Kulesa, P; Maini, P (Wiley, 2019)
The neural crest serves as a powerful and tractable model paradigm for understanding collective cell migration. The neural crest cell populations are well‐known for their long‐distance collective migration and contribution to diverse cell lineages during vertebrate development. If neural crest cells fail to reach a target or populate an incorrect location, then improper cell differentiation or uncontrolled cell proliferation can result. A wide range of interdisciplinary studies has been carried out to understand the response of neural crest cells to different stimuli and their ability to migrate to distant targets. In this critical commentary, we illustrate how an interdisciplinary collaboration involving experimental and mathematical modeling has led to a deeper understanding of cranial neural crest cell migration. We identify open questions and propose possible ways to start answering some of the challenges arising.